1995
DOI: 10.1007/bf03168085
|View full text |Cite
|
Sign up to set email alerts
|

Neural network reconstruction of single-photon emission computed tomography images

Abstract: Ah artificial neural network (ANN) trained on highquality medical tomograms or phantom images may be able to learn the planar data-to-tomographic image relationship with very high precision. As a result, a properly trained ANN can produce comparably accurate image reconstruction without the high computational cost inherent in some traditional reconstruction techniques. We have previously shown that a standard backpropagation neural network can be trained to reconstruct sections of single photon emission comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There have been a number of initial attempts at using machine learning and deep learning for medical image reconstruction. With the use of neural network, two classical papers from more than 20 years ago targeted SPECT image reconstruction [28,29]. More recently, dictionary learning, which is a contemporary machine learning approach, was adapted for MRI and CT image reconstruction [27,30,31].…”
Section: Pilot Resultsmentioning
confidence: 99%
“…There have been a number of initial attempts at using machine learning and deep learning for medical image reconstruction. With the use of neural network, two classical papers from more than 20 years ago targeted SPECT image reconstruction [28,29]. More recently, dictionary learning, which is a contemporary machine learning approach, was adapted for MRI and CT image reconstruction [27,30,31].…”
Section: Pilot Resultsmentioning
confidence: 99%
“…The development of neural network-based approaches to tomographic reconstruction began in 1995 with the landmark work by Kerr et al [73]. They demonstrated that a neural network could produce tomographic images of comparable accuracy to those used in its training.…”
Section: Neural Network-based Reconstruction Techniquesmentioning
confidence: 99%
“…In the framework of soft computing, the most popular approach to image reconstruction from projections is based on neural networks-a very popular and important tool of artificial intelligence systems for solving image processing problems, e.g., as described in (Cierniak and Rutkowski, 2000). The idea of a neural network applied to image reconstruction from projections is presented in (Kerr and Barlett, 1995a;Kerr and Barlett, 1995b;Kerr and Barlett, 1995c;Knoll et al, 1999;Munllay et al, 1994). Unfortunately, the supervised learning of algorithms described in these papers cannot lead to good performance.…”
Section: Introductionmentioning
confidence: 99%